2001
DOI: 10.1097/00002030-200109070-00005
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of intracellular HIV-1 mRNA correlates with HIV-1-specific immune responses in infected subjects on stable HAART

Abstract: These results suggest that HIV-1-specific immune responses correlate with evidence of ongoing HIV-1 replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 43 publications
4
33
0
1
Order By: Relevance
“…We demonstrated a correlation between the fold increase in HIV replication in intact cells and the fold increase in the ViraStim tubes relative to those in the EDTA tubes. We have previously shown the utility of SUSHI in measuring decreases in viral replication associated with antiretroviral therapy (21,22). In the present study, we demonstrate utility in the detection of increased viral replication in HIV-1 reservoirs infected with replication-competent virus, a potentially useful tool in the monitoring of eradication strategies.…”
Section: Discussionsupporting
confidence: 57%
“…We demonstrated a correlation between the fold increase in HIV replication in intact cells and the fold increase in the ViraStim tubes relative to those in the EDTA tubes. We have previously shown the utility of SUSHI in measuring decreases in viral replication associated with antiretroviral therapy (21,22). In the present study, we demonstrate utility in the detection of increased viral replication in HIV-1 reservoirs infected with replication-competent virus, a potentially useful tool in the monitoring of eradication strategies.…”
Section: Discussionsupporting
confidence: 57%
“…Cell-associated HIV RNA load, which reflects the level of viral transcription, including abortive transcription, also correlates with immune activation in untreated patients, patients on cART, and natural controllers (204,255,256,257). In patients on cART with undetectable viremia, HIV transcript loads correlate negatively with the CD4 T cell count (257) and positively with lymphoproliferative responses to HIV p24 antigen (258). Activa-tion stimulates transcription of persistent virus (257).…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of studies over the past several years have suggested that low levels of ongoing viral replication continue to persist and consequently prolong the overall half-life of HIV in patients receiving antiviral therapy (9)(10)(11)(12). These include the persistence of replication-competent virus (2-4), unintegrated proviral DNA, both linear (2) and circularized (13,14), and cell-associated HIV RNA (6,7,11,15,16). In addition, other studies have demonstrated that intensification of conventional antiviral regimens in patients who remained aviremic accelerated the decay of the latent HIV reservoir in the resting CD4 + T cell compartment (12) and further suppressed plasma viremia to well below the limit of detection (3.2-23 copies of HIV RNA per ml) (17).…”
Section: Introductionmentioning
confidence: 99%